The potential synergistic effect of combining doxorubicin with vorinostat in urothelial carcinoma therapy - Cheng-Huang Shen; Shou-Chieh Wang; Kah-Min Lee; Hsin-Ting Liu; Szu-Wei Huang; Jin-Yi Wu; Yi-Wen Liu (Heliyon)
Bladder cancer ranks as the 9th most common type of cancer worldwide. Approximately 70 % of bladder cancers are diagnosed as non-muscle invasive, and they are treated with transurethral resection followed by intravesical therapy. Doxorubicin is one of the effective cytotoxic drugs used in intravesical and systemic therapy, but its cardiotoxicity and nephrotoxicity limit therapeutic dosages. Vorinostat is an anticancer drug used to treat cutaneous T-cell lymphoma, and it demonstrates potent combination effects in various anticancer treatments. We aim to investigate the combined effects and mechanisms of doxorubicin and vorinostat in human bladder cancer cells. Human bladder cancer cells (5637 and BFTC 905) were used in this study. Cell viability of 5637 and BFTC 905 cells decreases in a time- and dose-dependent manner when treated with doxorubicin or vorinostat. Compared to the single drug treatment, the combination of doxorubicin and vorinostat synergistically induces cell death in 5637 and BFTC 905 cells. Combination drug treatment improves the expression of apoptosis-related proteins, including cleaved PARP, cleaved caspase 8, cleaved caspase 9, cleaved caspase-3, and γ-H2AX in both cell lines. Cell viability of combined treatment in both cell lines is partially restored by pre-treating with Z-VAD-FMK, a pan-caspase inhibitor. Z-VAD-FMK also completely reduced the protein expression of cleaved caspase 3 and γ-H2AX, suggesting that combining doxorubicin and vorinostat leads to DNA strand breaks and apoptosis. Pre-treatment with Z-IETD-FMK, a specific caspase 8 inhibitor, shows a slight recovery of cell viability in 5637 and BFTC 905 cells following combined treatment. Cleaved caspase 8, and γ-H2AX proteins in both cell lines are totally inhibited, and cleaved PARP is partially inhibited. Pre-treatment with Ac-LEHD-CMK, a specific caspase 9 inhibitor, no cell viability recovery in both cell lines. These results indicate that the combination of doxorubicin and vorinostat activates the caspase 8 and caspase 9 apoptosis pathways, and induces DNA strand breaks mainly via the caspase 8 pathway. The combination of doxorubicin and vorinostat also significantly inhibits the growth of BFTC 905 tumorspheres and BFTC 905 xenograft tumors in mice. In conclusion, our findings demonstrate that the combination of doxorubicin with vorinostat could potentially serve as a new treatment regimen for urothelial bladder cancer, for avoiding the high-dose side effect of doxorubicin.